Revival of Cultural Traditions of Katsky Stan on the Pages of Regional Publication "Katsky Chronicle" - Ekaterina D. Nevzorova (Publishing house "Sreda", 2020)
It is outlined that in the era of globalization, one of the key features of which is unification, there is a real danger of the disappearance of cultures of small ethnic groups. As a result, it becomes important to preserve and restore knowledge about their culture, customs and traditions. One of the bright projects dedicated to this topic is the "Katsky project", the main translator of ideas of which is the area publication "Katsky chronicle". The purpose of the research is to study the culture of the Katsky stan and ways of its revival. Hypothesis. In the course of the research, it was suggested that the journal "Katsky chronicle" is a way to revive and preserve the culture of the Katsky people. Methods of research. The research was carried out with the help of theoretic and empiric methods, the main method is the study of the historiographic database, which was compiled by the issues of the journal "Katsky chronicle" for the period from 1992 to 2017. The study of the journal's issues was conducted by analyzing the structure, content, sections, and language specifics of the journal (from the standpoint of semantics, phonetics, word formation, etc.). Results of research. The results confirmed the reflection of Katsky culture on the pages of the journal "Katsky chronicle": the authors of the articles used specific dialect katsky language which is a fundamental component of ethno-cultural identity of the Katsky people. Along with the language, the journal demonstrates folklore, publishes historical information about the Katsky stan and its inhabitants, symbols, specifics of the way of life and housekeeping, customs and traditions. The results also confirmed that in the era of globalization, in an atmosphere of universal similarity and uniformity, there are examples of preserving the uniqueness and ethno-cultural identity of communities of people in their places of local residence.